2008
DOI: 10.1103/physrevlett.100.028103
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkling of Vesicles during Transient Dynamics in Elongational Flow

Abstract: Recent experiments by Kantsler et al. [Phys. Rev. Lett. 99, 178102 (2007)10.1103/PhysRevLett.99.178102] have shown that the relaxational dynamics of a vesicle in external elongation flow is accompanied by the formation of wrinkles on a membrane. Motivated by these experiments we present a theory describing the dynamics of a wrinkled membrane. The formation of wrinkles is related to the dynamical instability induced by negative surface tension of the membrane. For quasispherical vesicles we perform analytical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 17 publications
2
63
0
Order By: Relevance
“…Strong shape deformations can occur only through a concave vesicle shape attained during compression, which is associated with a negative surface tension. One can expect the appearance of an instability, manifesting itself in the generation of higher order shape harmonics, similar to the wrinkling instability observed in a time-dependent elongation flow (25,26). Indeed, a significant third order harmonic was observed in TR at all values of S studied (see Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Strong shape deformations can occur only through a concave vesicle shape attained during compression, which is associated with a negative surface tension. One can expect the appearance of an instability, manifesting itself in the generation of higher order shape harmonics, similar to the wrinkling instability observed in a time-dependent elongation flow (25,26). Indeed, a significant third order harmonic was observed in TR at all values of S studied (see Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Recently, the dynamics of lipid vesicles in steady shear flow was intensively investigated [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A lipid vesicle can be considered as a microcapsule in the small limit of the shear modulus µ → 0.…”
Section: Introductionmentioning
confidence: 99%
“…Wrinkling has also been observed in experiments of vesicles by Kantsler et al [19] under time-dependent elongation flow [19]. It has been suggested that the winkling phenomena are related to the dynamical instability induced by negative surface tension of the membrane [20] during the vesicle deflation. These wrinkles usually are associated with higher [c]…”
Section: Relaxation Dynamics Of An Ellipse With Arclength Constraintmentioning
confidence: 51%
“…Kantsler et al also found that vesicle wrinkling may occur in time-dependent elongation flow [19,6]. It has been suggested that the winkling phenomena are related to the dynamical instability induced by negative surface tension of the membrane [20].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation